Nowcasting and forecasting of the magnetopause and bow shock—A status update. Issue 1 (31st January 2017) - Petrinec, S. M.; Redmon, R. J.; Rastaetter, L.
Abstract: There has long been interest in knowing the shape and location of the Earth's magnetopause and of the standing fast‐mode bow shock upstream of the Earth's magnetosphere. This quest for knowledge spans both the research and operations arenas. Pertinent to the latter, nowcasting and near‐term forecasting are important for determining the extent to which the magnetosphere is compressed or expanded due to the influence of the solar wind bulk plasma and fields and the coupling to other magnetosphere‐ionosphere processes with possible effects on assets. This article provides an update to a previous article on the same topic published 15 years earlier, with focus on studies that have been conducted, the current status of nowcasting and forecasting of geophysical boundaries, and future endeavors. Key Points: Recent spacecraft data sets have enabled the advancement of empirical models of the magnetopause and bow shock Improved computational modeling capabilities allow for real‐time of boundaries Metrics and skill scores are beginning to be effectively used to assess boundary forecasting accuracy